A Novel Locking Buttress Plate Designed for Simultaneous Medial and Posterolateral Tibial Plateau Fractures: Concept and Comparative Finite Element Analysis. Issue 4 (15th February 2023) - Yan, Bangji; Huang, Xiaotao; Xu, Yingxing; Zou, Chengshi
Abstract : Objective: The complex tibial plateau fractures involving both medial and posterolateral columns are of frequent occurrence in clinics, but the existing fixation system cannot deal with medial and posterolateral fragments simultaneously. Therefore, a novel locking buttress plate named as medial and posterior column plate (MPCP) was designed in this study to fix the simultaneous medial and posterolateral tibial plateau fractures. Meanwhile, the comparative finite element analysis (FEA) was conducted to investigate the discrepancy between MPCP and traditional multiple plates (MP + PLP) in their biomechanical characteristics. Methods: Two 3D finite element models of simultaneous medial and posterolateral tibial plateau fracture fixed with MPCP and MP + PLP system, respectively, was constructed. To imitate the axial stress of knee joint in ordinary life, diverse axial forces with 100, 500, 1000, and 1500 N were applied in the two fixation models, and then the equivalent displacement and stress nephograms and values were obtained. Results: The similar trend of displacement and stress increasing with the loads was observed in the two fixation models. However, several heterogeneities of displacement and stress distribution were found in the two fixation models. The max displacement and von Mises stress values of plates, screws, and fragments in the MPCP fixation model were significantly smaller than that in the MP + PLP fixation model, except for the max‐shear stress values. Conclusion: As a single locking buttress plate, the MPCP system showed the excellent benefit on improving the stability of the simultaneous medial and posterolateral tibial plateau fractures, compared with the traditional double plate fixation system. However, the excessive shear stress around screw holes should be paid attention to prevent trabecular microfracture and screw loosening. Abstract : Compared with traditional double plate fixation system, the MPCP system was beneficial to the placement of screws for posterolateral fragments fixation, and reduced the displacement and stress of fragments, and improved the stability of fractures in the treatment of medial column combined with posterolateral column of tibial plateau fractures.